Faktor – faktor yang mempengaruhi keputusan investasi mahasiswa - Oktaviani Ros Mema Karo; Murtanto Murtanto (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
The study examines how financial literacy, financial inclusion, and financial efficacy impact the investment decisions of economics and business students in Jakarta. It used a quantitative approach and collected data from 105 respondents through questionnaires. The multiple linear regression analysis with Eviews 12 revealed that the three independent variables positively and significantly affect investment decisions, explaining 89.09% of the variation. The findings highlight the importance of enhancing knowledge, access, and confidence in financial management to improve the investment decisions of college students. This study enhances our understanding of the financial behavior of young adults. It has implications for developing financial education programs and policies that promote responsible investment practices among college students. Public interest statements This research offers valuable insights into the factors influencing young people's investment decisions. Understanding the impact of financial knowledge, access to financial services, and confidence in managing money can assist college students in making wiser investment decisions.